Allergic contact dermatitis: epidemiology, molecular mechanisms, in vitro methods and regulatory aspects - Peiser, Matthias; Diepgen, Thomas L. (Cellular and molecular life sciences, 2012)
Contact allergies are complex diseases, and one of the important challenges for public health and immunology. The German ‘Federal Institute for Risk Assessment’ hosted an ‘International Workshop on Contact Dermatitis’. The scope of the workshop was to discuss new discoveries and developments in the field of contact dermatitis. This included the epidemiology and molecular biology of contact allergy, as well as the development of new in vitro methods. Furthermore, it considered regulatory aspects aiming to reduce exposure to contact sensitisers. An estimated 15-20% of the general population suffers from contact allergy. Workplace exposure, age, sex, use of consumer products and genetic predispositions were identified as the most important risk factors. Research highlights included: advances in understanding of immune responses to contact sensitisers, the importance of autoxidation or enzyme-mediated oxidation for the activation of chemicals, the mechanisms through which hapten-protein conjugates are formed and the development of novel in vitro strategies for the identification of skin-sensitising chemicals. Dendritic cell cultures and structure-activity relationships are being developed to identify potential contact allergens. However, the local lymph node assay (LLNA) presently remains the validated method of choice for hazard identification and characterisation. At the workshop the use of the LLNA for regulatory purposes and for quantitative risk assessment was also discussed.